Comparison of Voice Quality of Life in Early Stage Glottic Carcinoma Treated with Endoscopic Cordectomy Using Radiofrequency Microdissection Electrodes, Laser Cordectomy, and Radiotherapy - BİNNETOĞLU, ADEM; OYSU, ÇAĞATAY (MOSBY-ELSEVIER, 2021)
Purpose. To compare the quality of life of patients with early glottic carcinoma who have been treated using three treatment modalities: endoscopic cordectomy using radiofrequency microdissection electrodes (ECRM), transoral laser cordectomy, and radiotherapy (RT). ECRM, transoral laser cordectomy, and RT can all be used as alternatives to invasive open surgery to treat the early stages of glottic cancer such as stage T1. Patients treated using these different modalities could have different outcomes with respect to voice quality of life. Materials and Methods. The voice quality of life was measured in patients who underwent ECRM, transoral diode laser excision, or RT for early laryngeal cancer. Post-treatment quality of voice was assessed using the Turkish version of the Voice-Related Quality of Life questionnaire in all patients after 1 year of cancer-free survival. A comparison was then made between the outcomes of the three groups. Results. The total score of the ECRM group, when compared independently to that of the laser and the RT groups, was found to be statistically higher in both cases. However, no statistically significant differences were found between laser and RT groups in terms of any parameters. There was a statistically significant difference between the RT group and the other groups in terms of percentage jitter, percentage shimmer, and fundamental frequency (F0) (P < 0.05). While the RT group had the longest maximum phonation time (P < 0.001), no significant differences were found between the maximum phonation time of the ECRM and the laser groups (P < 0.001). Conclusions. Overall, the worst outcome with respect to voice quality of life is seen with ECRM. Since there were no significant differences in quality of life between the other two treatment modalities, it is recommended to leave the choice between RT and laser surgery up to the patient.
Keywords: Laryngeal cancer; Laser; Radiofrequency ablation; Radiotherapy; Voice quality; DIODE-LASER; SURGERY; CANCER; MICROSURGERY